The Image Base of Fairy-tale Formula in the Structure of Folklore Text (Based on Russian, Slovak, and Czech Fairy Tales and Their Translations) - Tyshchenko, Oleh; Figedyová, Marianna (Slavistica Vilnensis, 2023)
The article presents a comparative analysis of fairy-tale texts from the perspective of their structural, semantic, pragmatic, as well as linguistic and cultural features. Verbal and semiotic code of fairy tales has been reconstructed on the basis of their bidirectional translation (translation of Folk Russian Tales by A. Afanasiev into Slovak and Czech and, vice versa, Slovak and Czech fairy tales translation into Russian). The article considers fairy formulas, namely, initial, middle and final ones proceeding from the archetypal structure, value and semantic dominants, as well as concepts of folklore texts (transformations and variants of plots and allomotives, typology of images and names of fairy-tale characters through the lens of V. Propp, S. Neklyudov, E. Novik and others’ views). The units under scrutiny are described both in terms of their equivalence, figurative structure, and possible translation transformations, as well as ways of transferring culture-specific elements and pragmes into foreign cultural folklore and semiotic space. The approach applied in the article presupposes cultural and semantic reconstruction of the predominant conceptual spheres actualized in fairy tales, particularly the ones of giving, the Way, 'us' and 'them', happy end and marriage (Russian motif of wedding feast), oppositions of the living and the dead, functions of fairy-tale loci, such as emptiness, chaos and cosmogonic representations associated with them. Moreover, the research analyzes modal, temporal, and syntactic characteristics of fairy-tale formulas, lexical and semantic substitutions, as well as compensations and equivalents in the target text.
Keywords: initial; final and medial formulas; translation of fairy tales; archetypal model of the world; pragmatics of folklore text; translation transformations; allomotive; variant; reality